2015
DOI: 10.1182/blood-2015-06-649087
|View full text |Cite
|
Sign up to set email alerts
|

EHMT1 and EHMT2 inhibition induces fetal hemoglobin expression

Abstract: Key Points EHMT1/2 inhibition increases human γ-globin and HbF expression, as well as mouse embryonic β-globin gene expression. EHMT1/2 inhibition decreases H3K9Me2 and increases H3K9Ac at the γ-globin gene locus in adult human erythroid cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 41 publications
1
78
0
Order By: Relevance
“…Reduction of G9a expression levels inhibited lung and breast cancer cell proliferation, migration and invasion in vitro and suppressed primary tumor growth and metastasis in vivo [29] . Renneville [30] et al demonstrated in 2015 that knockdown of either EHMT1 or EHMT2 could significantly increase the expression of γ-globin genes, and the percentage of cells expressing hemoglobin F (HbF). This discovery may lead to a new therapy for sickle BIX01294, identified through a high-throughput screening, was the first reported [31,32] selective small molecule inhibitor of G9a and GLP, showing an IC 50 of 1.9 µmol/L for G9a and 0.7 µmol/L for GLP, separately.…”
Section: Ehmt1/2mentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of G9a expression levels inhibited lung and breast cancer cell proliferation, migration and invasion in vitro and suppressed primary tumor growth and metastasis in vivo [29] . Renneville [30] et al demonstrated in 2015 that knockdown of either EHMT1 or EHMT2 could significantly increase the expression of γ-globin genes, and the percentage of cells expressing hemoglobin F (HbF). This discovery may lead to a new therapy for sickle BIX01294, identified through a high-throughput screening, was the first reported [31,32] selective small molecule inhibitor of G9a and GLP, showing an IC 50 of 1.9 µmol/L for G9a and 0.7 µmol/L for GLP, separately.…”
Section: Ehmt1/2mentioning
confidence: 99%
“…The structure of BIX01294 consists of three parts: quinazoline, piperidine and diazepane subunits. Further structure-activity relationship (SAR) studies were conducted, including the extension of 7-methoxy into the target lysine binding channel and replacement of the benzyl group on the piperidine, represented by UNC0638 [30,33] , UNC0646 [34] and UNC0631 [34] . All three compounds showed high potency both in a fluorescence-based SAH-coupled assay (IC 50 : 4-19 nmol/L) and in the H3K9me2 In-Cell Western (ICW) assay (IC 50 : 25-81 nmol/L), with an excellent toxicity to function ratio range of 110-140 in MDA-MB-231 (breast carcinoma) cells compared with BIX01294 (<6).…”
Section: Ehmt1/2mentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, other investigators continue to identify new targets and small molecules that stimulate expression of fetal hemoglobin. These approaches include inhibition of G9a methyltransferase [7], inhibition of EHMT1 and EHMT2 histone methyltransferases [8], inhibition of lysine-specific demethylase 1 (LSD1) [9], and novel small molecule inducers of fetal hemoglobin identified in high-throughput screening [10, 11]. The robust efforts by many investigators to boost fetal hemoglobin expression using a wide variety of strategies represents the progress gained from long term investment in funding this field, raising promise for future therapeutics, but the pathway to drug development in any field is always long.…”
Section: Red Cells In Scdmentioning
confidence: 99%
“…Evidence continues to mount for roles of CMPs in the pathogenesis of such varied diseases as inflammation, arthritis, metabolic diseases, immune-modulatory diseases, neurological diseases, 12 and hematologic disorders. 13,14 Additionally, a clear role for CMP modulators has been demonstrated in inducing cell pluripotency as a mechanism toward eventual use in regenerative medicine. 15 As our understanding of the role of CMP modulators in these varied therapeutic indications matures, it will be important to see medicinal chemistry efforts expand into these as yet untested waters.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%